Refolding Process of Cysteine-Rich Proteins: Chitinase as a Model - Malihe Moghadam; Ali Ganji; Abdolreza Varasteh; Reza Falak; Mojtaba Sankian (Reports of Biochemistry and Molecular Biology, 2015)
Background: Recombinant proteins overexpressed in E. coli are usually deposited in inclusion bodies. Cysteines in the protein contribute to this process. Inter- and intra- molecular disulfide bonds in chitinase, a cysteine-rich protein, cause aggregation when the recombinant protein is overexpressed in E. coli. Hence, aggregated proteins should be solubilized and allowed to refold to obtain native- or correctly- folded recombinant proteins. Methods: Dilution method that allows refolding of recombinant proteins, especially at high protein concentrations, is to slowly add the soluble protein to refolding buffer. For this purpose: first, the inclusion bodies containing insoluble proteins were purified; second, the aggregated proteins were solubilized; finally, the soluble proteins were refolded using glutathione redox system, guanidinium chloride, dithiothreitol, sucrose, and glycerol, simultaneously. Results: After protein solubilization and refolding, SDS-PAGE showed a 32 kDa band that was recognized by an anti-chitin antibody on western blots. Conclusion: By this method, cysteine-rich proteins from E. coli inclusion bodies can be solubilized and correctly folded into active proteins.